The Role of Parenting in Fostering Independence Among Kindergarten Children: A Qualitative Case Study - Ilma'nunah, Lulu; Mulyana, Asep; Jazariyah, Jazariyah (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study explores the impact of parenting styles on the development of independence in early childhood. Focusing on five children in Group A of a kindergarten in Cirebon who demonstrated lower levels of independence, this qualitative case study involved participatory observation, semi-structured interviews, and documentation. Findings reveal that parenting significantly shapes children's independence, particularly in emotional regulation, responsibility, and confidence. Democratic parenting fostered the most positive outcomes, supporting both physical and psychological independence. In contrast, authoritarian parenting emphasized discipline but limited emotional development, while permissive and neglectful parenting often led to dependency and poor self-regulation. The study also highlights the influence of external caregivers, such as grandparents, whose indulgent behavior may undermine autonomy, even when democratic parenting is practiced at home. These findings underscore the need for consistent, responsive parenting and collaboration between home and school to foster independence in young children.